1998
DOI: 10.1103/physrevb.58.r8925
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the critical temperature onnin(BaCuO2

Abstract: ͑BaCuO 2 ͒ 2 /͑CaCuO 2 ͒ n superconducting superlattices have been grown by pulsed laser deposition for n ranging from 1 to 6. The critical temperature was found to depend strongly on the growth conditions. A maximum T c value of about 80 K ͑zero resistance temperature͒ was found for superlattices grown at high oxygen pressure ( P O 2 Ӎ0.8 mbar) and relatively high temperature (T g Ӎ600°C). The dependence of T c on the number n of CaCuO 2 layers ͑for superlattices grown exactly in the same conditions͒ was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…It was found that, the maximum value of T c is obtained for Nϭ3 and that, increasing N, the IL superconducting block becomes more and more underdoped, finally giving rise to an insulating behavior for NϾ12. 14,15 For the present study ͓͑Ba 0.9 , Nd 0.1 ͒CuO 2ϩx ͔ m /͓CaCuO 2 ͔ 2 (mϫ2) superlattices were deposited varying m in order to investigate the role of the coupling between successive (CaCuO 2 ) 2 conducting blocks. Thus the distance between successive IL blocks ranges from 8.5 Å ͑2ϫ2 superlattices͒ to 21 Å ͑5ϫ2 superlattices͒.…”
mentioning
confidence: 99%
“…It was found that, the maximum value of T c is obtained for Nϭ3 and that, increasing N, the IL superconducting block becomes more and more underdoped, finally giving rise to an insulating behavior for NϾ12. 14,15 For the present study ͓͑Ba 0.9 , Nd 0.1 ͒CuO 2ϩx ͔ m /͓CaCuO 2 ͔ 2 (mϫ2) superlattices were deposited varying m in order to investigate the role of the coupling between successive (CaCuO 2 ) 2 conducting blocks. Thus the distance between successive IL blocks ranges from 8.5 Å ͑2ϫ2 superlattices͒ to 21 Å ͑5ϫ2 superlattices͒.…”
mentioning
confidence: 99%
“…The overall experimental studies have suggested that the superconductivity is mainly confined at the interface between CCO and STO [6,[10][11][12]. Differently from previous cuprate/cuprate heterostructures [5,13,14], now the spacer between the superconducting blocks is not a cuprate, but it is STO. The CCO/STO interfaces are thus very similar to the IL/CR native interface of HTS.…”
mentioning
confidence: 99%
“…For larger n values, T c (n) shows a smooth decrease, which is well explained taking into account the decrease of the effective hole concentration per single CuO 2 plane due to the increase of the total number of CuO 2 planes in the IL block. 17 For nϽ2, T c shows a sharp drop. A striking result of this investigation was that the occurrence of a non integer number n of CaCuO 2 unit cells in the IL block does not affect the T c of these artificial structures.…”
Section: Introductionmentioning
confidence: 94%